Competitive Bidding in Auctions with Private and Common Values - Jacob K. Goeree; Theo Offerman (Tinbergen Institute, 2000)
The objects for sale in most auctions possess both private and common value elements. This salient feature has not yet been incorporated into a strategic analysis of equilibrium bidding behaviour. This paper reports such an analysis for a stylised model in which bidders receive a private value signal and an independent common value signal. We show that more uncertainty about the common value has a negative effect on efficiency. Information provided by the seller decreases uncertainty, which raises efficiency and seller's revenues. Efficiency and revenues are also higher when more bidders enter the auction.
Keywords: C72; D44; 330; Auctions; inefficiencies; information disclosure; competition; Auktionstheorie; Informationsökonomik; Wettbewerb; Theorie